Sundanese Tafsīr as Lived Religion: Vernacular Exegesis and Multicultural Islamic Education in Urban Indonesia - Alam Tarlam; Eti Nurhayati; Septi Gumiandari; Ahmad Asmuni (UIN Sunan Gunung Djati Bandung, 2025)
This article examines Sundanese tafsīr as lived religion by analyzing Tafsir Ayat Suci Lenyepaneun by Moh. E. Hasim as a form of vernacular Qur’anic exegesis that operates as multicultural Islamic education within a plural urban society. The study aims to demonstrate that locally grounded tafsīr functions not only as a textual interpretation of the Qur’an but also as a pedagogical practice through which Islamic values are taught, experienced, and internalized in everyday social life. The study employs a qualitative descriptive design that integrates phenomenological and hermeneutic approaches. Data were collected through textual analysis of Tafsir Ayat Suci Lenyepaneun, participant observation of tafsīr study circles, and in-depth interviews with Muslim religious leaders, congregants, and non-Muslim residents in an urban neighborhood of Bandung. The data were analyzed thematically to trace how Qur’anic interpretations are articulated, transmitted, and internalized as lived ethical practices. The findings reveal three main patterns. First, the use of the Sundanese language enables Qur’anic messages to operate simultaneously at cognitive and affective levels, facilitating deep internalization of values such as justice, empathy, and respect for difference. Second, tafsīr functions as an oral and contextual pedagogy, in which key verses are conveyed through narratives and social illustrations that cultivate inclusive religious ethics and emotional self-restraint. Third, the internalization of tafsīr-based values produces cross-communal effects, reflected in harmonious interreligious relations and non-Muslim residents’ perceptions of safety and social cohesion. These findings imply that vernacular Qur’anic tafsīr can serve as an effective community-based model of multicultural Islamic education beyond formal educational institutions, contributing to social harmony in plural urban societies. The originality of this study lies in its empirical demonstration of how local tafsīr operates as lived religion and in positioning vernacular exegesis as a transformative pedagogical resource within the field of religious studies.